Science in the Social Media Age: Profiles of Science Blog Readers. (March 2018) - Jarreau, Paige Brown; Porter, Lance
Science blogs have become an increasingly important component of the ecosystem of science news on the Internet. Through a survey of 2, 955 readers of 40 randomly selected science blogs, we created profiles of science blog users. Super users indicated reading science blogs for a wide range of reasons, including for community-seeking purposes. One-way entertainment users indicated reading blogs more for entertainment and ambiance. Unique information-seeking users indicated reading blogs more for specific information not found elsewhere. But regardless of science blog users' motivations to read, they are sophisticated consumers of science media possessing high levels of scientific knowledge.